Trans Memori Imajinasi Dalam Pewarisan Nilai Monumental Pertunjukan Wayang Kulit Bagi Masyarakat Hindu di Bali - Wicaksandita, I Dewa Ketut; Hendra, Santosa; Saptono, Saptono; Sutirtha, I Wayan; Wicaksana, I Dewa Ketut (Jayapangus Press, 2025)
Memory transfer (memory trance) conceptually involves actively remembering, realizing, and inheriting values of greatness, survival, and stability in performing arts. Imagination, used to affirm memory transfer, creates mental images that emphasize large, impressive objects, ideas, or concepts, significantly influencing the inheritance of the monumental value of Balinese traditional wayang kulit performances. This research aims to first identify memory trance based on imagination in inheriting Balinese wayang kulit's monumental value; second, analyze the significance of memory trances in this inheritance. A phenomenological approach (psychology-imagination) and instrumental aesthetic theory support the qualitative research. Findings include: first, imagination memory trance reveals action phases based on imagination behavior, such as 'imagination' (transmutation of objects by the subject), ‘creativity and mental imagery’ (transformation through metacognition), ‘cultural context’ (value clarification and internalization), and 'monumental value' (understanding the majestic value). Second, the significance of imaginary memory transience impacts active behavior in inheriting Balinese wayang kulit's monumental value. It examines the audience's aesthetic experience from imaginary images presented by the puppeteer and transforms artistic sources into aesthetic elements involving socio-cultural trends, creating 'dialectics' and 'catharsis' for audience appreciation. Additionally, it involves internalizing socio-religious values, building involvement, and vertical-horizontal existence, and forming the image of wayang as monumental art.